2022
DOI: 10.17645/mac.v10i3.5300
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Observers or Advocates for Societal Transformation? Role Orientations of Constructive Journalists in Germany

Abstract: Since the 2010s, a new type of journalism has emerged, especially in North America and Western Europe, called constructive journalism. Its basic idea is to complement classic problem-centered reporting by covering problem-solving approaches that could inspire the recipients. It has been harshly criticized, especially for its alleged proximity to advocacy or activism. To clarify the role orientations of the protagonists of this trend, a survey of all German journalists that call themselves constructive or solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…By adopting these roles, journalists can contribute to fostering a more informed and engaged citizenry, ultimately strengthening democratic societies. Some of the journalistic roles proposed by Krüger et al (2022), Hermida and Mellado (2020), Standaert et al (2019, Abdenour et al (2018Abdenour et al ( , 2021, Dahmen et al (2019), Li (2023), Thier and Namkoong (2023), Mäder and Rinsdorf (2023), Vos (2018, 2017), Ojala and Pöyhtäri (2018), Hanitzsch et al (2016), Tandoc and Peters (2015), Mellado and Dalen (2014), and Dalen et al (2012) in their investigations have been taken and expanded, and particularly, they have been reoriented towards the explanatory and constructive nature of the journalism model that has been exposed in this work. Even some journalistic functions, such as contextualization, promotion of public interest, dialogue, and understanding, as well as motivation or inspiration to action and commitment to communities and societies, are considered fundamental beyond constructive journalism or solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By adopting these roles, journalists can contribute to fostering a more informed and engaged citizenry, ultimately strengthening democratic societies. Some of the journalistic roles proposed by Krüger et al (2022), Hermida and Mellado (2020), Standaert et al (2019, Abdenour et al (2018Abdenour et al ( , 2021, Dahmen et al (2019), Li (2023), Thier and Namkoong (2023), Mäder and Rinsdorf (2023), Vos (2018, 2017), Ojala and Pöyhtäri (2018), Hanitzsch et al (2016), Tandoc and Peters (2015), Mellado and Dalen (2014), and Dalen et al (2012) in their investigations have been taken and expanded, and particularly, they have been reoriented towards the explanatory and constructive nature of the journalism model that has been exposed in this work. Even some journalistic functions, such as contextualization, promotion of public interest, dialogue, and understanding, as well as motivation or inspiration to action and commitment to communities and societies, are considered fundamental beyond constructive journalism or solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, constructive journalists have eight role dimensions, including the social integrator, transformation agent, Active Watchdog, Emotional Storyteller, and Innovation Reporter. Krüger et al (2022) found that these journalists aim to control political and business elites, motivate participation, and contribute to social change. They are not only solution-oriented but also work normatively, politicized, and attached to specific issues, and may also be watchdogs of political and business elites in a Western tradition.…”
Section: Literature and Analysismentioning
confidence: 99%